THERMOPLASTIC STARCH BASED POLYMER BLENDS: SYNTHESIS, CHARACTERISATION AND ANALYSIS OF STABILITY - J V, Benlin Giftna; S, Begila David (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the present work, thermoplastic starch from cassava starch was grafted with epoxy derived from castor oil polyol. Fresh starch, prepared from cassava root tuber was polymerised and blended with epoxy in different compositions leading to variations in properties. The synthesized polymer blends could be filled or reinforced with nano-silica for effective functionality by eco-friendly means. The synthesized blends were characterized using FT-IR, Scanning Electron Microscope, EDAX and the water uptake percentage and soil bio-degradability were studied. Further, mechanical and thermal stability of the blends were characterised. With further developments, these starch-based nanocomposites can be expected to replace conventional polymers for variety of applications.